Effect of the REACT strategy on senior high school students’ achievement in molecular genetics - Quainoo, Benedicta Abeka; Otami, Charles Deodat; Owusu, Kofi Acheaw (LUMAT: International Journal on Math, Science and Technology Education, 2021)
Molecular genetics, a key concept in biology, is found to be very difficult for students at the senior high school level. A situation largely blamed on teachers’ instructional approaches. Since the Relating, Experiencing, Applying, Cooperating and Transferring (REACT) strategy is reported to be an effective pedagogical approach for improving students’ understanding of science concepts, in this paper, we sought to explore its effectiveness on Senior High School students’ achievement in molecular genetics in Ghana. To do this, the embedded mixed methods research design was employed. Two intact biology classes selected through simple random sampling were assigned as experimental and control groups and taught with the REACT strategy and the conventional approach respectively. Quantitative data were obtained with pre-test-post-test control group design and analysed with Independent sample t-test and ANOVA. The qualitative data on students’ perception of learning with the REACT strategy was obtained through interviews and analysed thematically. The findings showed that the REACT strategy was more effective for teaching molecular genetic compared with the conventional approach. Although REACT could not bridge the gap between low and high achievers in that group, the performance of low achievers in the REACT group was at par with high achievers in the conventional group. Students perceived the opportunity to search and share information as well as relate new concepts to prior learning provided by the REACT strategy to have facilitated their understanding of concepts in molecular genetics. It is recommended that biology teachers use the REACT strategy to teach concepts students find problematic.